Computerized cognitive practice effects in relation to amyloid and tau in preclinical Alzheimer's disease: Results from a multi‐site cohort. Issue 1 (20th March 2023) - Young, Christina B.; Mormino, Elizabeth C.; Poston, Kathleen L.; Johnson, Keith A.; Rentz, Dorene M.; Sperling, Reisa A.; Papp, Kathryn V.
Abstract: Scalable cognitive paradigms that provide metrics such as the Computerized Cognitive Composite (C3) may be sensitive enough to relate to Alzheimer's disease biomarkers in the preclinical clinically unimpaired (CU) stage. We examined CU older adults ( n = 3287) who completed alternate versions of the C3 approximately 51 days apart. A subset of CU with abnormal amyloid also completed tau positron emission tomography (PET) imaging. C3 initial performance and practice effects were examined in relation to amyloid status and continuous regional tau burden. Initial C3 performance was associated with amyloid status across all participants, and with tau burden in the medial temporal lobe and early cortical regions in CU with abnormal amyloid. Short‐term practice effects were associated with reduced tau in these regions in CU with abnormal amyloid, but were not associated with amyloid status. Thus, computerized cognitive testing repeated over a short follow‐up period provides additional insights into early Alzheimer's disease processes.